The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Insight into using multi-omics analysis to elucidate nitrogen removal mechanisms in a novel improved constructed rapid infiltration system: Functional gene and metabolite signatures - Qiya Sun; Zhipeng Zhang; Qian Ping; Lin Wang; Yongmei Li (Water Research, 2024)

Revealing synergistic mechanisms of biochar-assisted microbial electrolysis cells in enhancing the anaerobic digestion performance of waste activated sludge: Extracellular polymeric substances characterization, enzyme activity assay, and multi-omics analysis - Dunjie Li; Qian Ping; Rongrong Mo; Wenjie Guo; Shuang Zhang; Lin Wang; Yongmei Li (Water Research, 2024)

Regulation of freshwater filamentous green algae (Cladophora) and its impact on malodorous volatile organic sulfur compound (DMS) by biomanipulation - Yutai Dai; Yu Lin; Ping Deng; Jiping Chen; Weijie Li; Qiang Gao; Hong Shen; Qiutong Peng; Mo Chen; Xuwei Deng (Science of The Total Environment, 2024)

International mangrove carbon sink research analysis - Youpeng Xiao; Chenglin Li; Xuxia Li; Yudong Wang; Ping Sun; Xu Xu; Haipeng Wang; Yimeng Chen; Junchuan Lin; Guisong Huang; Zhenguo Huang; Wang Xu (Regional Studies in Marine Science, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Integration of automatic discontinuity identification and multi-scale hierarchical modeling for stability analysis of highly-jointed rock slopes - Ya-ping Wang; Jia-wen Zhou; Jun-lin Chen; Yu-chuan Yang; Fei Ye; Hai-bo Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Tracking the transformation of extracellular polymeric substances during the ultraviolet/peracetic acid disinfection process: Emphasizing on molecular-level analysis and overlooked mechanisms - Yizhe Ding; Qiya Sun; Qian Ping; Lin Wang; Yongmei Li (Water Research, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Ti-doped fly ash‑aluminum‑iron based composite coagulant for efficient fluoride removal from mine drainage over a wide pH range - Zhiwei Lin; Xuezhi Li; Chunhui Zhang; Wenjing Lu; Yanxin Li; Yiyun Li; Ping Qiao (Journal of Water Process Engineering, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Acid-assisted pretreatment for sweet elephant grass in choline chloride/glycerol DES: Experimental and mechanism study - Yining Zhang; Weizhen Xie; Weidong Li; Yue Tang; Jiali Wu; Lihui Gan; Ling-Ping Xiao; Xu Zhang; Lu Lin; Xing Tang (Chemical Engineering Journal, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Insight into the effect of CaO2 addition on the prevalence and removal of antibiotic resistance genes during anaerobic sludge fermentation under ambient conditions - Xiaoxia Chen; Qian Ping; Qinyuan Lu; Zepeng Yang; Lin Wang; Yongmei Li (Journal of Environmental Chemical Engineering, 2024)

Synthesis and characterization of Ce-BiOBr/Bi2S3 catalyst with enhanced catalytic activity for organic dye reduction under dark - Mengistu Tadesse Mosisa; Pengkun Zhang; Binghong Wu; Longyan Chen; Zhengjie Su; Ping Li; Hanya Zhang; Ambar Farooq; Ting Huang; Adugna Boke Abdeta; Osman Ahmed Zelekew; Dong-Hau Kuo; et al. (Journal of Environmental Chemical Engineering, 2024)

Enhancing interfacial electron transfer and photoelectrochemical kinetics for efficient water-treatment strategy through N-doped carbon dots modified PhC2Cu - Xiaoyu Zhang; Yishun Wang; Zili Lin; Qingman Chen; Minghao Liu; Dezhu Liu; Zhenchao Li; Ping Chen; Wenying Lv; Guoguang Liu (Environmental Pollution, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Unexpected enhancement effects of phosphate on co-immobilization of uranyl arsenate under acidic conditions - Penggang Li; Ping Zhang; Aishu Li; Lin Yu; Mengying Si; Qi Liao; Zhihui Yang; Weichun Yang (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

A clinical-radiomics nomogram based on spectral CT multi-parameter images for preoperative prediction of lymph node metastasis in colorectal cancer - Qian Li; Rui Hong; Ping Zhang; Liting Hou; Hailun Bao; Lin Bai; Jian Zhao (Clinical & Experimental Metastasis, 2024)

Microfluidics, an effective tool for supporting phage display-A review - Liang Li; Hang Yuan; Qin Li; Kai Li; Ping Lin (Analytica Chimica Acta, 2024)

Seasonal changes of plankton community and its influencing factors in subtropical coastal marine areas revealed by eDNA-based network analysis - Xiaoqi Lin; Kunhuan Li; Hancheng Zhao; Yan Gao; Zonghang Zhang; Lin Wang; Xinjie Wang; Edmond Sanganyado; Zhao Zheng; Qilin Gutang; Sailan Liu; Ping Li; et al. (Frontiers in Marine Science, 2024)
Introduction Coastal marine ecosystems are among the most ecologically and socio-economically dynamic regions on Earth, and the study of eukaryotic planktonic communities is an important aspect of aquatic ecology. It is essential to monitor plankton biodiversity and identify influencing factors in order to measure human effects on coastal waters and help contribute to ecosystem preservation. Environmental DNA (eDNA) metabarcoding analysis is an advanced toolfor detecting the presence of aquatic organisms, which has revolutionary significance for biodiversity monitoring and real-time detection of wild environments. Methods In this study, eDNA metabarcoding was used to study seasonal changes in eukaryotic plankton communities in subtropical coastal waters of the northern South China Sea, to explore how various trophic groups affect the complexity and stability of the species network. Results The results showed that the summer interaction network is looser and had has reduce biodiversitycompared to the spring interaction network. As an important part of the planktonic community, the abundance and diversity of algae reflect the interactions between different species and the influence of environmental factors on the dominant species, particularly temperature and nutrients. In addition, producer diversity set the basis for species network complexity and indirectly affected network stability, while consumer diversity and its flexible predation strategies may directly lead to differences in network stability across seasons. There were close correlations among species interaction, environmental factors and species diversity. Discussion This study can help us understand the ecosystem functions throughout the year and the complex interactions of planktonic communities from a multiple trophic level perspective, and provide effective methods for sustainable resource utilization and ecological environmental protection in the future.

Mercury sources, transport, and transformation in rainfall-runoff processes: Mercury isotope approach - Ruolan Li; Junyao Yan; Chuan Wang; Shaochen Yang; Lin Zhang; Tao Peng; Wei Zhu; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Research and application of comprehensive detection methods for geological structural planes in drill and blast tunnels - Peng Yang Qiao; Zao Bao Liu; Yong Ping Li; Chao Lin; Guo Ying Yan (Journal of Applied Geophysics, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Neurobehavioral toxicity induced by combined exposure of micro/nanoplastics and triphenyltin in marine medaka (Oryzias melastigma) - Peiran Lin; Ling Liu; Yuqing Ma; Renyan Du; Chuansen Yi; Ping Li; Yanan Xu; Haiyang Yin; Le Sun; Zhi-Hua Li (Environmental Pollution, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Assessments of 12 Commercial Species Stocks in a Subtropical Upwelling Ecosystem Using the CMSY and BSM Methods - Lin Chen; Peilong Ju; Zhenbin Lu; Cui Liang; Bin Chen; Jianguo Du; Ping Li (Fishes, 2024)
Twelve commercial species exploited in the eastern Guangdong and southern Fujian waters were assessed using the Catch-Maximum Sustainable Yield (CMSY) and Bayesian Schaefer Model (BSM) methods. The carrying capacity (k), intrinsic rate of population growth (r), maximum sustainable yield (MSY), and relative biomass (Bend/k and B/BMSY) were estimated. The current stock status was defined by B/BMSY and fishing mortality (F/FMSY). The results indicate that seven stocks were overfished or below safe biological limits (B/BMSY 1), two stocks were in a recovery phase (0.5 1, F/FMSY

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

The composition of soil fungal communities is more dependent on biocrust type than on shrub cover in the Mu Us Desert - Lin Xu; Chaonan Li; Wenjun Xiong; YongPing Kou; Ping Zou; Bingjie Jiao; Minjie Yao; Junming Wang; Bingchang Zhang; Xiangzhen Li (Fungal Ecology, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Deciphering the influence of salinity stress on the biological aniline degradation system: Pollutants degradation performance and microbial response - Qi He; Bin Tan; Meng Li; Junhao Su; Bing Lin; Nan-ping Wu; Hao-nan Shen; Jia-jing Chen; Qian Zhang (Environmental Research, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Integrated analysis reveals the immunotoxicity mechanism of BPs on human lymphocytes - Qiujin Zhang; Mengzhen Li; Ping Wang; Xiao Lin; Keng Po Lai; Zhixiang Ding (Chemico-Biological Interactions, 2024)

Downregulation of OATP2B1 by proinflammatory cytokines leads to 5-ASA hyposensitivity in Ulcerative colitis - Ping Li; Jun Luo; Yiming Jiang; Xiaoyi Pan; Minlei Dong; Binxin Chen; Jinhai Wang; Hui Zhou; Huidi Jiang; Yangri Duan; Nengming Lin (Chemico-Biological Interactions, 2024)

Effects of Salt Content and Freeze-Thaw Conditions on Dynamic characteristics and its microscopic mechanism of Chloride Silty Clay - Yaqin Zhang; Ping Yang; Lin Li; Ting Zhang; Linliang Han (Cold Regions Science and Technology, 2024)

A Test System for Microwave-Assisted Dual-Mode Mechanical Cutting of Hard Rock Under True Triaxial Compression - Xia-Ting Feng; Xiang-xin Su; Cheng-xiang Yang; Feng Lin; Shi-ping Li; Jiu-yu Zhang; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)
This paper introduces a test system for microwave-assisted dual-mode mechanical cutting of hard rock under true triaxial compression. The test system was developed by Northeastern University, China, to simulate the cutting and breaking of hard rock by a tunnel boring machine (TBM). The test system is mainly composed of a dual-mode mechanical cutting subsystem, a true triaxial loading subsystem and a high-power microwave presplitting subsystem. The system performs dual-mode cutting under true triaxial stress, applies a single sensor to monitor the three-dimensional force of the cutter head, and integrates the reduction in the vibration and resistance to torsion during the cutting process. Mechanical cutting tests of basalt under different amounts of microwave irradiation and true triaxial stress conditions were conducted in Chifeng, Inner Mongolia, China. The results showed that microwave radiation presplitting effectively improved the efficiency of mechanical rock breaking. However, after 180 s of microwave irradiation, true triaxial high stress inhibited the mechanical breaking of basalt in terms of the overall excavation depth. During the tests, each system performed stably. The test results verified the reliability of the test system.

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Litoamentenes A–K, eleven undescribed cembranoids with cytotoxicity from the South China Sea soft coral Litophyton amentaceum - Yuan Zong; Jun-Jie Yang; Kai Li; Yan-Fang Pei; Hui-Yue Hou; Yue Zhang; Ci-Li Wang; Ping-Lin Li (Phytochemistry, 2024)

VGluT2 neuron subtypes in the paraventricular thalamic nucleus regulate depression in paraquat-induced Parkinson’s disease - Yu Zhang; Yihua Jiang; Zhen Yu; Yinhan Li; Xinpei Lin; Yali Weng; Zhenkun Guo; Hong Hu; Wenya Shao; Guangxia Yu; Fuli Zheng; Ping Cai; et al. (Journal of Hazardous Materials, 2024)

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Insights into nitrogen-doped BiOBr with oxygen vacancy and carbon quantum dots photocatalysts for the degradation of sulfonamide antibiotics: Actions to promote exciton dissociation and carrier migration - Zhenchao Li; Chenghui Wen; Daguang Li; Zheng Fang; Zili Lin; Dezhu Liu; Yishun Wang; Xiaoyu Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

The origins of odor (β-cyclocitral) under different water nutrient conditions: Algae or submerged plants? - Yu Lin; Chaoyue Cheng; Yutai Dai; Weijie Li; Jiping Chen; Mo Chen; Ping Xie; Qiang Gao; Xiaoyue Fan; Xuwei Deng (Science of The Total Environment, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Adsorption behavior of CuO doped GeS monolayer on the thermal runaway gas evolution in lithium battery energy storage systems - Jinjie Wang; Bo Lin; Ping Wang; Lu-Qi Tao; Yuan Zhang; Siquan Li (Journal of Environmental Chemical Engineering, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Role of rainfall temporal distribution on effective infiltration in the loess slope and prediction model - Gan Lin; Hengxing Lan; Ping Li; Langping Li; Shijie Liu; Weifeng Sun (Engineering Geology, 2024)

Maize Soybean Relay Strip Intercropping Increases N Uptake by Coordinating Crop Configuration to Improve Root Physiological Activity - Xinyue Peng; Xueli Yang; Junbo Ren; Lida Yang; Ping Lin; Kai Luo; Xiaoting Yuan; Jiangli Luo; Yuze Li; Wenyu Yang; Taiwen Yong (Journal of Soil Science and Plant Nutrition, 2024)

Severe nitrogen leaching and marked decline of nitrogen cycle-related genes during the cultivation of apple orchard on barren mountain - Yuwen Shen; Haining Chen; Haitao Lin; Ping Liu; Xiaozong Song; Yanan Ma; Mingli Li; Wensheng Gao; Lingling Song (Agriculture, Ecosystems & Environment, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

A study on expression of GRP78 and CHOP in neutrophil endoplasmic reticulum and their relationship with neutrophil apoptosis in the development of sepsis - Jinchuan Zhao; Ping Yang; Li Lu; Tao Yi; Yunfeng Li; Wei Mao; Qin Zhou; Ke Lin (Journal of Biosciences, 2024)

Application of artificial intelligence in (waste)water disinfection: Emphasizing the regulation of disinfection by-products formation and residues prediction - Yizhe Ding; Qiya Sun; Yuqian Lin; Qian Ping; Nuo Peng; Lin Wang; Yongmei Li (Water Research, 2024)

Comparison of different sewage sludge pretreatment technologies for improving sludge solubilization and anaerobic digestion efficiency: A comprehensive review - Pan Zhou; Dunjie Li; Cong Zhang; Qian Ping; Lin Wang; Yongmei Li (Science of The Total Environment, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

Improved Pb(II) removal by D001 resin with a facile nanoscale α-FeOOH modification - Bing Li; Zhiyi Deng; Xueying Lin; Weiting Chen; Ping Li; Jinhua Wu (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Insight into using hydrochar to alleviate ammonia nitrogen inhibition during anaerobic digestion of waste activated sludge: Performance, metagenomic and metabolomic signatures - Lin Wang; Yunpeng He; Yuting Zhu; Qian Ping; Yongmei Li (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Potential of perennial sorghum for biogas production: Pretreatment with yeast-contained inoculants during anaerobic storage - Xiaolong Tang; Chaosheng Liao; Shufeng Zhou; Cheng Chen; Lin Li; Guangrou Lu; Xiaokang Huang; Mingjie Zhang; Chao Chen; Ping Li (Fuel, 2024)

Experimental study on strength characteristics and constitutive behavior of frozen chloride silty clay - Yu Tang; Ping Yang; Lin Li; Zhiliang Zhou (Cold Regions Science and Technology, 2024)

A global synthesis of the patterns of genetic diversity in endangered and invasive plants - Zhi-Zhou He; Gisela C. Stotz; Xiang Liu; Jia-Jia Liu; Yu-Guo Wang; Ji Yang; Lin-Feng Li; Wen-Ju Zhang; Peng Nan; Zhi-Ping Song (Biological Conservation, 2024)

Optimization of Microwave Presplitting Iron Ore to Improve Mechanical Mining Efficiency - Feng Lin; Xia-ting Feng; Shi-ping Li; Jiu-yu Zhang; Xiang-xin Su; Tian-yang Tong (Rock Mechanics and Rock Engineering, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Chronic ammonia stress caused disorder of intestinal microbiota and damaged intestinal structure and function in yellow catfish (Pelteobagrus fulvidraco) - Lin Luo; Senyue Liu; Baipeng Chen; Fulong Li; Yongqiang Deng; Xiaoli Huang; Yi Geng; Ping Ouyang; Defang Chen (Aquaculture, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

A comprehensive investigation to the fate of phosphorus in full-scale wastewater treatment plants using aluminum salts for enhanced phosphorus removal - Qian Ping; Zhipeng Zhang; Wenjie Guo; Lin Wang; Yongmei Li (Science of The Total Environment, 2024)

Underlying the mechanisms of pathogen inactivation and regrowth in wastewater using peracetic acid-based disinfection processes: A critical review - Yuqian Lin; Yunpeng He; Qiya Sun; Qian Ping; Manhong Huang; Lin Wang; Yongmei Li (Journal of Hazardous Materials, 2024)

Experimental study on the morphology of turbulent diffusion flames with different aspect ratios under slope conditions - Chunxiang Liu; Tairun Lai; Hao Zhang; Ping Huang; Kaihong Lin; Yuchao Lin; Man Li (Fuel, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Warming and wetting-induced soil acidification triggers methanotrophic diversity loss and species turnover in an alpine ecosystem - Chaonan Li; Changting Wang; Ping Zou; Lin Xu; Haijun Liao; Nan Lan; Li Lei; Wenjun Xiong; Weidong Kong; Junming Wang; Xiangzhen Li (CATENA, 2024)

Application of an absolute reference frame for methane clumped-isotope analyses - Qingmei Liu; Jiacheng Li; Wenmin Jiang; Yun Li; Mang Lin; Wen Liu; Yanhua Shuai; Haizu Zhang; Ping'an Peng; Yongqiang Xiong (Chemical Geology, 2024)

Chemical constituents from the stem of Ficus pumila - Wen-Lin Xiao; Wen-Hao Chen; Wei Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2024)

Soil erosion sensitivity and prediction for hilly areas of Hubei Province, China, using combined RUSLE and LSTM models - Yaodong Ping; Pei Tian; Li Luo; Yahui Guo; Yuwei Gong; Zhanliang Zhu; Yongsheng Cui; Lin Chen (Journal of Soils and Sediments, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Experimental and numerical investigation of the expansion mechanism of beam-end expansion devices in large-span bridge - Tao Liao; Juan Song; Jun Lai; Kai Wang; Ping Wang; Zhiheng Li; Jingmang Xu; Yao Qian; Junke Lin (Engineering Structures, 2024)

The designation of intrinsic flame-retarding vinyl ester resins with high mechanical property, optical transparency and degradability - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang; De-Yi Wang (Chemical Engineering Journal, 2024)

Toll-Like Receptor 4 Deficiency Ameliorates Propofol-Induced Impairments of Cognitive Function and Synaptic Plasticity in Young Mice - Qiao-Ding Dai; Kang-Song Wu; Li-Ping Xu; Yan Zhang; Na Lin; Yao Jiang; Chong-Yu Shao; Li-Da Su (Molecular Neurobiology, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)